Implementasi Program Anti-Perundungan untuk Melindungi Kesehatan Mental Siswa di SMA Dharma Karya UT Kota Tangerang Selatan - Iqbal Maulana Saputra; Ati Kusmawati (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Bullying in schools is a serious issue that affects students’ mental health and therefore needs to be addressed through specific programs that create a safe, comfortable, and healthy environment. Increasing public awareness of the dangers of bullying has encouraged the emergence of anti-bullying programs in schools, including at SMA Dharma Karya UT. This study aims to analyze the implementation of such a program with four main objectives, namely to understand its execution, assess its effectiveness, identify existing obstacles, and provide relevant recommendations for improvement. The research method employed is quantitative with a descriptive approach using questionnaires developed based on program implementation and mental health indicators, tested for validity and reliability, and analyzed with SPSS version 25. The research sample involved 98 students from grades X, XI, and XII, selected through a representative quota sampling technique. The results show a significant relationship between the anti-bullying program and students’ mental health, with a correlation coefficient of 0.760 indicating a strong relationship. The program explains 57.8% of the variance in mental health, while 42.2% is influenced by other external factors. Simple regression analysis produced a constant of 43.783 and a coefficient of 1.814, meaning improvements in program implementation are directly proportional to improvements in mental health. Hypothesis testing confirmed significance with a value of 0.000 < 0.05, thus accepting the alternative hypothesis. The anti-bullying program has proven to be effective and can serve as a reference for other schools.